Implementasi Pelaksanaan Program Kampus Mengajar Angkatan 7 UPT SPF SMP Negeri 55 Makassar - Umair Ahmad; Hurriah Ali Hasan (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This activity aims to provide opportunities to students, how they can work in the education sector how they become teachers of course this is also a means to develop themselves and activities and creativity in the wild university, other than that we also observe so that we know how the teaching and learning process, the condition of the teaching staff and the quantity of students and teachers themselves in addition to the method of observation we also conduct research methods at UPT SPF SMP Negeri 55 Makassar. 1) the object of research is the implementation of teaching campus Force 7 at UPT SPF SMP Negeri 55 Makassar. Data collection is done with observation techniques that can be concluded that the teaching and learning process that occurs in the school is going well where the use of technology in the application of the teaching and learning process is going well. As for their character development, if seen they are still lacking in implementing a characterization system where they still often fight teachers, do not want to be set, and speak loudly to teachers, then their characters to their friends, there is still often bullying, even to fights. As for the activities that we do outside the classroom, such as taking care of the green house, playing and interacting more with students, in addition we carry out a literacy and numeracy festival which contains various competitions, from rank 1 poetry, speech, guess the picture, and traditional competitions, these activities are carried out so that students are able to hone their soft skills.